The financial well-being of Nigerian students in Universiti Putra Malaysia - Chikezie, Obilaonu Columbus; Sabri, Mohamad Fazli (Zes Rokman Resources, 2017)
Due to the high cost of living in Malaysia many students have become more concerned about their financial well-being and more careful with their spending in order to have a comfortable life or live comfortably in the future. The acquisition of knowledge on the way students develop good and bad financial behaviours will help other individuals that seek to improve their financial behaviours make better decisions and choices in terms of financial issues. There is need for everyone to have proper understanding of issues related to financial management and well-being because financial challenges do not only affect university or college students but also workers and other individual that low, middle and high income earners. The purpose of this study is to examine the factors that determine the financial well-being of Nigerian students studying in Malaysia. The sample of the study was conducted among 420 Nigerian postgraduate and undergraduate students in Universiti Putra Malaysia. Through the use of stratified sampling technique, the sample for this study was selected and data was collected using structured questionnaire. Findings of the study showed that majority of the respondents were males between the age range of 18-29 years. Results of this study showed that there was a significant relationship between financial well-being and financial socialization, financial behaviour and money attitude except for financial literacy. Multiple regression showed that six variables contributed significantly to the variance of financial well-being and they are financial behaviour, financial socialization, money attitude (effort), money attitude (obsession), money attitude (retention). Based on the findings, it can be concluded that only few Nigerian students in UPM had high level of financial well-being while the rest had moderate and low level. This means that there is still need for the money attitude, financial socialization and financial behaviour to be strengthened since they are part of the predicting variables of financial well-being among the respondents.